Polarization-multiplexed dual-comb fiber laser based on an all-polarization-maintaining cavity configuration - Rao, Bingjie; Li, Mingkun; Yang, Xiguang; Yan, Lulu; Chen, Xin; Yuan, Ru; Zhang, Pan; Zhang, Shougang (Frontiers in Physics, 2022)
We present a polarization-multiplexed, Er-doped, dual-comb fiber laser based on an all-polarization-maintaining cavity configuration. The dual-comb fiber laser can easily realize the self-starting mode-locking operation due to the nonlinear amplifying loop mirror (NALM) with nonreciprocal phase shifter. Owing to the sharing of NALM part, the two outputs from this laser configuration have the same center wavelength with a small different repetition rate (∆frep). In the free-running operation, the standard deviation of relative stability for Δfrep of 2.09 kHz is measured to be 1.59 Hz and the full-width at half-maximum of the relative beat note between the two frequency combs in optical frequency domain is measured to be∼1 kHz. The results show that the two frequency combs from this laser configuration have high relative stability and mutual coherence.